Respiration and the watershed of spinal CSF flow in humans - Dreha-Kulaczewski, Steffi (Sci Rep, 2018)
The dynamics of human CSF in brain and upper spinal canal are regulated by inspiration and connected to the venous system through associated pressure changes. Upward CSF flow into the head during inspiration counterbalances venous flow out of the brain. Here, we investigated CSF motion along the spinal canal by real-time phase-contrast flow MRI at high spatial and temporal resolution. Results reveal a watershed of spinal CSF dynamics which divides flow behavior at about the level of the heart. While forced inspiration prompts upward surge of CSF flow volumes in the entire spinal canal, ensuing expiration leads to pronounced downward CSF flow, but only in the lower canal. The resulting pattern of net flow volumes during forced respiration yields upward CSF motion in the upper and downward flow in the lower spinal canal. These observations most likely reflect closely coupled CSF and venous systems as both large caval veins and their anastomosing vertebral plexus react to respiration-induced pressure changes.